Relevansi Sosiologi Pengetahuan Karl Mannheim dalam Konteks Pendidikan Agama Islam di Era Kontemporer - ., Ubaidillah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The purpose of this study is to analyze the application of Karl Mannheim's sociology of knowledge theory in Islamic religious education in the contemporary era, with a focus on the role of ideology and utopia in shaping the curriculum and teaching of Islam. The library method in this study was used to explore literature related to Karl Mannheim's sociology of knowledge, Islamic religious education, and its application in contemporary education. This study adopts a descriptive-qualitative approach by analyzing Mannheim's works and literature that discusses the dynamics of Islamic religious education in Indonesia, both traditional and modern. The main focus is to examine how ideology and utopia influence Islamic religious learning, as well as the relevance of integrating religious knowledge with general science in the context of globalization. The results of the study show that in Islamic religious education in the contemporary era, ideology and utopia have a major influence on the formation of religious knowledge. Religious education is often hampered by conservative ideologies that prioritize tradition and reject innovation, ignoring developments in science and technology. However, a more progressive integration of utopia can encourage changes in teaching methods, allowing Islamic religious education to be more relevant to the challenges of the times. This study also found a gap between traditional religious education and the need to adapt religious knowledge to social and global realities. Therefore, it is necessary to update the educational methodology in order to create a generation that not only understands religion, but is also able to play an active role in an increasingly developing society.